A Semite : a memoir of Algeria - Guénoun, Denis, 1946- (Columbia University Press, 2014)
In this memoir, the author excavates his family's past and portrays an imposing, enigmatic father. René Guénoun was a teacher, pioneer, and supporter of Algerian independence. Although his Jewish family was rooted in Algeria, he inherited French citizenship. He taught science in a French lycée and belonged to the French Communist Party. The Guénouns had little interest in Israel and considered themselves at home in Algeria; yet because he supported Algerian independence, René outraged his French neighbours and was expelled from Algeria by the French paramilitary Organisation Armée Secrète.